Analisis Faktor – Faktor Yang Mempengaruhi Minat Generasi Milenial Memilih Bank Syariah (Studi Kasus Pada Masyarakat Kecamatan Makasar Kota Jakarta Timur) - Muktar, Irvan; Fajar, Ade; Salama, Hartini (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2025)
This study examines the influence of knowledge, religiosity, location, and service on the interest of the millennial generation in choosing an Islamic bank in Makassar District, East Jakarta. The purpose of this study is to be able to find out the factors of knowledge, religiosity, location and service that affect the millennial generation's interest in choosing Islamic Banks. This study uses a descriptive quantitative method The sample size is 100 residents, with a questionnaire used for data collection. The results of the study show that knowledge, religiosity, and location have a negative and insignificant influence on the interest of Generation Y in choosing Islamic banks in the Makassar area. The service had a positive and significant influence, with a count of 3,296 > a table of 1,968 and a significance value of 0.001 < 0.05. However, the variables of knowledge, religiosity, location, and services had a significant influence, with a count of 6.390 > 2.47 and a significance value of 0.000 < 0.05. The study concluded that the millennial generation's interest in choosing an Islamic bank is influenced by four factors: knowledge, religiosity, location, and service. This research can be a reference for Islamic banking services to improve the quality and attractiveness of the millennial generation.